Implementing a multi-vehicle multi-route spatial decision support system for efficient trash collection in Portugal - Santos, Luís (2008)
More efficient vehicle routing can improve a firm's competitive advantage or increase the efficiency by which governmental agencies supply public services. More efficient routing can also reduce traffic congestion and air pollution which are growing problems in many urban areas. Unfortunately, the identification of the optimal solution to most vehicle routing problems is computationally intractable. This article presents a user-friendly spatial decision support system (SDSS) to generate vehicle routes for multiple-vehicle routing problems that serve demand located along arcs and at nodes of the transportation network. The SDSS incorporates a geographical information system (GIS) and heuristic solution procedures to generate routes, system-wide data, and maps, as well as individual vehicle route maps, directions, and data quickly. It accommodates realistic system specifics such as vehicle capacity and time constraints and network constraints such as one-way streets, and prohibited turns. The system was tested for trash collection in Coimbra, Portugal. In addition, the SDSS can be used for "what-if" analysis related to possible changes to input parameters such as vehicle capacity and maximum driving time.